2015
DOI: 10.21608/asnj.2015.182381
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of educational health problems among liver cirrhosis patients to improve their Quality Of Life in Minia University Hospital

Abstract: Back ground: Liver cirrhosis is a serious chronic disease, affects most of body systems and reduce patient's quality of life (QOL). It needs a nursing guidelines to be developed according to patient's needs. Aim of this study was to assess educational needs of liver cirrhosis patients, (assessment of QOL domains, liver cirrhosis health problems and complications) to improve their quality of life. Descriptive research design has been used to carry out this study. Patients and methods:The study sample included 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…However, there were insignificant difference between pre and post intervention regarding -experienced bodily pain‖ and experienced abdominal pain‖. Taha et al, (2015) who studied "Assessment of educational health problems among liver cirrhosis patients to improve their Quality Of Life in Minia University Hospital", as regards the domain of abdominal symptoms, the majority of the patients in the study sample felt abdominal bloating a little of time, pain and discomfort most of time during the last two weeks in the time of data collection. Also Furate et al, (2013) who studied "The Impact of Self-Care Instructional program on Quality of Life of Patients with Liver cirrhosis at El-Kasr EL Ainy Cairo University Hospital" found that, In relation to the domain of abdominal symptoms, the majority of the patients in the study sample felt abdominal distension, pain and discomfort most of time during the last two weeks in the time of data collection, more than one third of them felt abdominal pain and discomfort all time, while the minority of them felt it little of time.…”
Section: Effect Of Nursing Intervention On Health Profile and Symptom...mentioning
confidence: 91%
“…However, there were insignificant difference between pre and post intervention regarding -experienced bodily pain‖ and experienced abdominal pain‖. Taha et al, (2015) who studied "Assessment of educational health problems among liver cirrhosis patients to improve their Quality Of Life in Minia University Hospital", as regards the domain of abdominal symptoms, the majority of the patients in the study sample felt abdominal bloating a little of time, pain and discomfort most of time during the last two weeks in the time of data collection. Also Furate et al, (2013) who studied "The Impact of Self-Care Instructional program on Quality of Life of Patients with Liver cirrhosis at El-Kasr EL Ainy Cairo University Hospital" found that, In relation to the domain of abdominal symptoms, the majority of the patients in the study sample felt abdominal distension, pain and discomfort most of time during the last two weeks in the time of data collection, more than one third of them felt abdominal pain and discomfort all time, while the minority of them felt it little of time.…”
Section: Effect Of Nursing Intervention On Health Profile and Symptom...mentioning
confidence: 91%